Some Aspects of Spiritual and Aesthetic Problematics of the Silver Age in the Works of M. Vrubel and A. Blok - Tsvetaeva, Marina N.; Sokurova, Olga B. (Actual Problems of Theory and History of Art, 2017)
The article is dedicated to some crucial similarities in the spiritual paths, life philosophy, andartistic symbols of M. Vrubel and A. Blok. All religious, mystic, aesthetic searches, insights, and faus of the Silver Age were concentrated in the works of the mentioned personalities. The problems and contradictions that can be found in the individual ways of the artist and the poet as well as in the atmosphere of that time are analyzed from the views of the Orthodox outlook in its theological and aesthetic wholeness. This particular method of research enables us to get even deeper into the problematics of the Silver Age. This paper also highlights the image of Vrubel’s and Blok’s Demon whose routes go straight to the well-known poem by M. Lermontov. The evolution of these two images and their authorial interpretation lead to a conclusion that both the poet and the artist managed to overcome the temptation of individualism and aestheticism of their time. As a result of constantspiritual struggle, by the end of their lives, both of them saw the light through their experience, suffering, repentance, and the search for truth.
Keywords: Silver Age; Vrubel; Blok; symbolism; theological and aesthetic wholeness; image semantics; knowledge of God; demonology; aestheticism